Phytochemical profiles and inhibitory effect on free radical-induced human erythrocyte damage of Dracaena draco leaf: A potential novel antioxidant agent - Santos, R.P. (2011)
The present study reports for the first time the metabolite profile and antioxidant activity of aqueous extract obtained from Dracaena draco L. leaf. Volatiles profile was determined by HS-SPME/GC-IT-MS, with 34 compounds being identified, distributed by distinct chemical classes: 2 alcohols, 5 aldehydes, 16 carotenoid derivatives and 8 terpenic compounds. Carotenoid derivative compounds constituted the most abundant class in leaf (representing 45% of total identified compounds). Phenolics profile was determined by HPLC/DAD and 9 constituents were identified: 2 hydroxycinnamic acid derivatives – 5- O-caffeoylquinic and 3,5-O-dicaffeoylquinic acids; 4 hydroxycinnamic acids – caffeic, p-coumaric, ferulic and sinapic acids and 3 flavonol glycosides – quercetin-3-O-rutinoside, kaempferol-3-O-glucoside and kaempferol-3-O-rutinoside. The most abundant phenolic compound is quercetin-3-O-rutinoside (representing 50.2% of total polyphenols). Organic acids composition was also characterised, by HPLC–UV and oxalic, citric, malic and fumaric acids were determined. Oxalic and citric acids were present in higher amounts (representing 47%, each). The antioxidant potential of this material was assessed by the ability to protect against free radical-induced biomembrane damage, using human erythrocyte as in vitro model. Leaf extract strongly protected the erythrocyte membrane from haemolysis (IC50 of 39 ± 11 lg/ml), in a time- and concentration-dependent manner. This is the first report showing that D. draco leaf is a promising antioxidant agent.